Peritoneal dissemination of ovarian cancer: role of MUC16-mesothelin interaction and implications for treatment. Issue 2 (1st February 2018) - Coelho, Ricardo; Marcos-Silva, Lara; Ricardo, Sara; Ponte, Filipa; Costa, Antonia; Lopes, Jose Manuel; David, Leonor
ABSTRACT: Introduction : Peritoneal dissemination is a particular form of malignant progression in ovarian cancer, preceding hematogenic or lymphatic dissemination. Thus, prevention of peritoneal implantation of cancer cells is envisioned to inhibit neoplastic dissemination and therefore prolong disease remission and patient's survival. Areas covered : An extended review on the role of MUC16 (CA125) and mesothelin (MSLN), expressed in a high percentage of ovarian carcinomas, indicate that this duet is relevant for the contact between cancer cells and mesothelial cells in homotypic (cancer cell-cancer cell) and heterotypic (cancer cell-mesothelial cell) interactions. This review discusses the reasons underlying the clinical failure of immunotherapeutic strategies targeting MUC16. Clinical data on MSLN targeting agents such as antibody-based immunotoxins or antibody drug conjugates are also reviewed. The promising anti-tumor effect of CAR-T cells directed to MUC16 or MSLN is emphasized. New emerging strategies specifically disrupting the MUC16-MSLN interaction are at the forefront of this review, including TRAIL ligands bound to MSLN targeting MUC16 expressing cells and single chain monoclonal antibodies and immunoadhesins recognizing MSLN-MUC16 binding domains. Expert commentary : Based on existing evidences the authors advocate that agents targeting MUC16-MSLN may add to the therapeutic armamentarium directed to abrogate peritoneal homing of ovarian cancer.